Comparison of fate and transport of atrazine in corn and rubber plantation soils - W. Sinlapathorn; D. Keochanh; P. Phuinthiang; N. Nawinwattana; M. Jindakaraked; P. Kajitvichyanukul (Lowland Technology International, 2018)
The rubber and corn plantation soils in Nan province were investigated for the fate and transport behavior of the atrazine. The biodegradation, adsorption, photodegradation, and infiltration of atrazine in both soils were conducted. The kinetic rates of each experiment were calculated and reported. Results illustrated that the microbials in the soils have a high tendency in consuming the atrazine in both corn and rubber soils. The corn soils with the biodegradation rate as 0.2523 Kg/mg-min had higher kinetics rate than rubber soil with 0.1357 Kg/mg-min. Langmuir isotherm best described the adsorption of atrazine in both corn and rubber soils. The sorption capacity of atrazine adsorption on the rubber soil (1/qm = 9.7095) was much higher than the corn soil (1/qm = 0.5195). The amount of herbicide residue bonded on soil after application in the rubber soil was slightly higher than the corn soil, and the photolytic rate in the rubber soil is much higher than that in the corn soil. From the mass balance, atrazine in water was detected in the higher amount than in the soil for both corn and rubber soils. The infiltration rate in corn soil was 13.1 mm/hr while that in rubber soil was 11.8 mm/hr. The mass of atrazine in the leachate is in the range of 32.1-75.3% in both corn and rubber soils during 36 hours of infiltration. This experiment is the scientific evidence supporting that the contamination of atrazine in groundwater has high tendency to occur in the extreme application of the atrazine to the agriculture soil.